Analoge Klangsynthese zur Vermittlung von Grundkenntnissen der Signalverarbeitung an Studierende nicht-technischer Fachrichtungen - Krumme, Matthias; Webersen, Manuel; Claes, Leander; Webersen, Yvonne (Fortschritte der Akustik - DAGA 2020)

ASSESSING THE FUTURE: METHODS AND CRITERIA - Gräßler, Iris; Thiele, Henrik; Scholle, P. (Proceedings of the DESIGN 2020 16th International Design Conference)
Abstract As time-to-market is getting shorter, customer needs have to be identified as early as possible in product development. Correctly applied, corporate foresight can give a glimpse into the future to anticipate such needs and thus gain a competitive advantage. A support tool to choose the appropriate method of foresight is not available yet. Thus, a literature study on foresight methods in industry is performed and a novel decision support tool is proposed which avoids high entrepreneurial risks. Based on the findings, potentials for future work are identified for different types of methods.

A Scrum Agile Integrated Development Framework - Thiele, Henrik; Weber, Sebastian; Reichwein, Jannik; Bartolo, Joseph A.; Tchana, Yvan; Jimenez, Lucas; Borg, Jonathan C. (Proceedings of the DESIGN 2020 16th International Design Conference, 26. - 29. Okt. 2020)

Lesekompetenz fördern. Ein Manual für das LIFE-Programm zur Stärkung der Zusammenarbeit von Schule und Elternhaus - Bonanati, Sabrina; Greiner, Christian; Gruchel, Nicole; Buhl, Heike M.

Improving scenario-technique by a semi-automatized consistency assessment based on pattern recognition by artificial neural networks - Gräßler, Iris; Scholle, Philipp; Thiele, Henrik (Proceedings of the DESIGN 2020 16th International Design Conference; 26. - 29. Okt. 2020)

Mechatronischer Entwurf eines geregelten Federungssystems für mittelschwere gepanzerte Kettenfahrzeuge - Gense, Alexander

Produkttolerante Automation zellenbasierter Fertigungssysteme - Bertelsmeier, Fabian

On efficiently solvable cases of Quantum k-SAT - Gharibian, Sevag; Aldi, Marco; de Beaudrap, Niel; Saeedi, Seyran (Communications in Mathematical Physics)

Towards a Critical Theory of Communication as Renewal and Update of Marxist Humanism in the Age of Digital Capitalism - Fuchs, Christian (Journal for the Theory of Social Behaviour)

Communicative Socialism/Digital Socialism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Alltagsleben und Alltagskommunikation im Coronavirus-Kapitalismus - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Everyday Life and Everyday Communication in Coronavirus Capitalism - Fuchs, Christian (tripleC: Communication)

The Utopian Internet, Computing, Communication, and Concrete Utopias - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Erich Fromm and the Critical Theory of Communication - Fuchs, Christian (Humanity & Society)

The Ethics of the Digital Commons - Fuchs, Christian (Journal of Media Ethics)

Vida e comunicação cotidianas no capitalism da coronavirus - Fuchs, Christian (MATRIZes)

Chemical and Morphological Transition of Poly(acrylonitrile)/Poly(vinylidene Fluoride) Blend Nanofibers during Oxidative Stabilization and Incipient Carbonization - Wortmann, Martin; Frese, Natalie; Mamun, Al; Trabelsi, Marah; Keil, Waldemar; Büker, Björn; Javed, Ali; Tiemann, Michael; Moritzer, Elmar; Ehrmann, Andrea; Hütten, Andreas; Schmidt, Claudia; et al. (Nanomaterials)
Thermally stabilized and subsequently carbonized nanofibers are a promising material for many technical applications in fields such as tissue engineering or energy storage. They can be obtained from a variety of different polymer precursors via electrospinning. While some methods have been tested for post-carbonization doping of nanofibers with the desired ingredients, very little is known about carbonization of blend nanofibers from two or more polymeric precursors. In this paper, we report on the preparation, thermal treatment and resulting properties of poly(acrylonitrile) (PAN)/poly(vinylidene fluoride) (PVDF) blend nanofibers produced by wire-based electrospinning of binary polymer solutions. Using a wide variety of spectroscopic, microscopic and thermal characterization methods, the chemical and morphological transition during oxidative stabilization (280 °C) and incipient carbonization (500 °C) was thoroughly investigated. Both PAN and PVDF precursor polymers were detected and analyzed qualitatively and quantitatively during all stages of thermal treatment. Compared to pure PAN nanofibers, the blend nanofibers showed increased fiber diameters, strong reduction of undesired morphological changes during oxidative stabilization and increased conductivity after carbonization.

Humidity-Mediated Anisotropic Proton Conductivity through the 1D Channels of Co-MOF-74 - Javed, Ali; Strauss, Ina; Bunzen, Hana; Caro, Jürgen; Tiemann, Michael (Nanomaterials)
Large Co-MOF-74 crystals of a few hundred micrometers were prepared by solvothermal synthesis, and their structure and morphology were characterized by scanning electron microscopy (SEM), IR, and Raman spectroscopy. The hydrothermal stability of the material up to 60 °C at 93% relative humidity was verified by temperature-dependent XRD. Proton conductivity was studied by impedance spectroscopy, using a single crystal. By varying the relative humidity (70–95%), temperature (21–60 °C), and orientation of the crystal relative to the electrical potential, it was found that proton conduction occurs predominantly through the linear, unidirectional (1D) micropore channels of Co-MOF-74, and that water molecules inside the channels are responsible for the proton mobility by a Grotthuss-type mechanism.

A modular, scalable open-hardware platform for project-based laboratory courses in electrical engineering studies - Hetkämper, Tim; Krumme, Matthias; Dreiling, Dmitrij; Claes, Leander (SEFI 48th Annual Conference Proceedings - Engaging Engineering Education)

Online-Lehre 2020 – Eine medienwissenschaftliche Perspektive. Diskussionspapier Nr. 10 - Bohnenkamp, Björn; Burkhardt, Marcus; Grashöfer, Katja; Hlukhovych, Adrianna; Krewani, Angela; Matzner, Tobias; Missomelius, Petra; Raczkowski, Felix; Shnayien, Mary; Weich, Andreas; Wippich, Uwe
Die Autor*innen werfen einen medienwissenschaftlichen Blick auf die Online-Lehre des Sommersemsters 2020. Dabei betrachten sie unter anderem den Unterschied von klassischen Hörsälen zu den neuen, virtuellen Lernräumen, die aber auch physische Elemente beinhalten. Dabei regen sie an, den Einsatz von Lehr-Lern-Plattformen kritisch zu diskutieren und insgesamt die Lehre mit andauernder Medienreflexion zu begleiten. Ein zentraler Punkt des Papiers ist das Aufzeigen von Inklusions- und Exklusionspotenzialen von Online-Lehre. Vermeintliche Selbstverständnisse spielen hier eine Schlüsselrolle. So wird zum Beispiel häufig eine gewisse technische Infrastruktur seitens der Studierenden vorausgesetzt, die nicht immer vorhanden ist. Andererseits entfallen physische Barrieren, die in Lehrgebäuden vorhanden wären. Die Autor*innen mahnen, bei der Konzeption von Online-Lehre zu vermeiden, nicht-behinderte Personen als die Norm anzunehmen und stattdessen von verschiedenen Körperlichkeiten her zu denken, um die positive Potenziale dieses Lehrmodus zu nutzen. Das Diskussionspapier widmet sich auch ausführlich dem Einsatz von (digitalen) Tools, die weniger als Werkzeuge, denn als Medien der Lehre verstanden werden.